Analysis of the Implementation of the Generic Regional Health Information System (SIKDA) at Simpang Tiga Health Center Pekanbaru City: Analisis Pelaksanaan Sistem Informasi Kesehatan Daerah (SIKDA) Generik Di Puskesmas Simpang Tiga Kota Pekanbaru - Fitri Verawati; Zainal Abidin; Reno Renaldi; Dami Yanthi; M.Dedi Widodo (Badnur Medisa Group, 2022)
The application of the Generic Regional Health Information System at the Community Health Center as a user aims to provide convenience for officers in carrying out reporting activities between sections and also for activities in reporting to the Health Office by using the Generic Regional Health Information System for online patient management. It is hoped that the results of the application of the Generic Regional Health Information System will be input for the benefit of management in preparing a health program planning and is expected to be used as a monitoring system for Community Health Center services by the Head of the Community Health Center and the Health Office to be more effective. This research is a qualitative research with a case study approach. The types of data used are primary data and secondary data. Primary data were obtained from direct observation, in-depth interviews, and document review. The informants of this study consisted of the Head of the Public Health Center, the Person in Charge of the Generic Regional Health Information System, the Operator of the Generic Regional Health Information System, the Police Officer, the Drug Warehouse & Pharmacy Officer and the Cashier of the Simpang Tiga Health Center. The results showed that the implementation of the Generic Regional Health Information System at the Simpang Tiga Health Center was still running up to the registration flow, so it was not interrelated between programs in accordance with the regulations set by the Government. Human resources who operate the Regional Health Information System still have adequate and not in accordance with the minimum educational standards, besides that the operators who run the Regional Health Information System have never received. Existing facilities and infrastructure still do not support the operation of the Generic Regional Health Information System, ranging from network and computer disturbances, which are still insufficient for the implementation of a complete Regional Health Information System flow. Therefore, it is hoped that the puskesmas can pay attention to the existing constraints, so that the operation of the Generic Regional Health Information System runs optimally.